Uwolnić alchemika: zabiegi Zygmunta III na dworze cesarskim o wypuszczenie z więzienia w Pradze Michała Sędziwoja. Nowe źródła - Skowron, Ryszard (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2019)
The article presents the efforts of Sigismund III Vasa at the imperial court to free the eminent Polish alchemist Michał Sędziwój (Michael Sendivogius) from Prague prison. The analyzed correspondence and instructions for emissaries depict diversified mechanisms of king’s action in this matter.
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne